Perjanjian Baku yang di Atur Otoritas Jasa Keuangan Pada Pinjaman Online - Danova, Muhamad Secha Aulia; Nugroho, Widhi Cahyo (Media Hukum Indonesia (MHI), 2025)
The growth of online lending services in Indonesia faces a dilemma between expanding financial access and the proliferation of exploitative practices, such as unilateral interest rate hikes and unauthorized modifications of repayment deadlines. This study analyzes the regulations by the Financial Services Authority (OJK), specifically OJK Regulation No. 77/2016 (POJK 77/2016) and OJK Regulation No. 10/2022 (POJK 10/2022), in protecting consumers from unfair practices. It also examines the disharmony between OJK’s sectoral legal framework and Indonesia’s Civil Code (KUHPerdata) and Law No. 8/1999 on Consumer Protection. Using a normative legal research method, this study integrates legal analyses of conflicts between the principle of contractual freedom (Article 1338 of the Civil Code) and the prohibition of inequitable clauses under the Consumer Protection Law.The findings reveal that while OJK regulations normatively prohibit exploitative clauses, inconsistencies with national law create legal loopholes exploited by online lenders. Unilateral clauses, such as interest rate increases and repayment deadline alterations, remain widespread due to the lack of harmonization between contractual freedom and the principle of consumer rights balance. OJK’s administrative sanctions are deemed ineffective, as they are disproportionate to the economic gains of lending platforms, while disguised fee practices result in effective interest rates exceeding legal limits. An analysis of court rulings shows that abusive clauses are more frequently invalidated under the Consumer Protection Law than under OJK regulations, indicating weak enforceability of OJK’s sectoral rules.This study recommends regulatory harmonization by strengthening consumer protection principles in OJK regulations, enhancing corporate criminal sanctions, and adopting artificial intelligence-based audit technologies. The academic contribution lies in critiquing the paradox of contractual freedom in Indonesia’s fintech ecosystem, while policy recommendations aim to balance digital financial innovation with consumer.